P2.12 Differences in uptake, characteristics, and testing history of clients of getcheckedonline during scale-up to urban, surburban and rural communities in british columbia, canada. (8th July 2017) - Haag, Devon; Salway, Travis; Thomson, Kimberly; Bondyra, Mark; Karlsson, Maja; Bannar-Martin, Sophie; Colangelo, Elizabeth; Grennan, Troy; Wong, Jason; Corneil, Trevor Reyes; Hoyano, Dee; Krajden, Mel; et al.
Abstract : Introduction: In Sept 2014, the BC Centre for Disease Control (BCCDC) launched GetCheckedOnline (GCO), an online testing service for STI/HIV which is integrated with clinical and public health services and developed to reduce testing barriers. Based on a successful pilot in urban Vancouver (BC's largest city) and alignment with regional health authority testing priorities, GCO was expanded to five other urban, suburban and rural communities across BC in Feb 2016. Here we examine differences in GCO uptake between Vancouver and expansion sites from the first year of scale-up in British Columbia (BC). Methods: We used routinely collected GCO program data in combination with BC Public Health Laboratory testing data to describe differences between GCO clients in Vancouver and expansion sites. We compared demographic characteristics and testing history as well as key program measures including service uptake (percent creating a GCO account who submitted specimens) and positivity rates (percent positive of specimens submitted). Results: Between Feb-Dec 2016, of 2397 clients creating accounts, 1297 (54%) submitted specimens; uptake was slightly lower in expansion sites (577 specimens, 51%) vs. Vancouver (720, 57%; p=0.001), with comparable positivity rates (6% vs. 5%; p=0.77). Compared to Vancouver, GCO clients in expansion sites were more likely to be younger (20–24 years of age) (20% vs. 13%) and symptomatic (20% vs. 14%), and less likely to be men who have sex with men (22% vs. 42%; p≤0.001 for all). GCO clients in expansion sites were more likely to be testing for the first time for both HIV (22% vs. 9%) and STI (16% vs. 9%; p<0.001). Conclusion: Scale-up of GCO to five smaller urban, suburban and rural communities across BC demonstrated differences in uptake and populations reached, including greater engagement of individuals not previously tested. Our study highlights the importance of differing regional contexts on the impact of online testing services and the need for their evaluation during scale-up.